Analysing the Characteristics of Educational Innovation: A Literature Review of Theory and Practice - Juli Setio; Rama Satria; Karoma; Fajri Ismail (Universitas Muhammadiyah Palu, 2024)
This research aims to identify and clarify the main characteristics of educational innovation through a literature review of theory and practice. The method used was a literature study with a qualitative approach, analysing various literature sources from journals, books and research reports. The results showed that the main characteristics of educational innovation include the use of technology, pedagogical change, student engagement and curriculum flexibility. Diffusion of innovation, constructivist learning and social systems theories support these findings. Evaluations of innovation practices such as e-learning, project-based learning and the use of digital media show improvements in learning quality. This research provides a comprehensive understanding of educational innovation and is an important reference for policy makers, educators and researchers in education.